AIP Conference Proceedings 2009
DOI: 10.1063/1.3156490
|View full text |Cite
|
Sign up to set email alerts
|

Development of a diagnostic aid for bacterial infection in wounds

Abstract: Infection of wounds during hospitalisation often induces morbidity and sometimes mortality. The delay in patient recovery and subsequent increased length of hospital stay also has economic consequences. Standard techniques for microbiological detection are surface swabbing and wound biopsy culture. Surface swabbing is the most commonly used technique mainly because is quite inexpensive and is not invasive but can give only a representation of surface infection and analysis is also time consuming. Infected woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In addition, microbiological culture results are only available after a few days. Two earlier studies [15,16] have explored the potential of electronic noses to fulfil the need for accurate and fast detection of wound infection in clinical practice. They demonstrated that electronic noses are able to discriminate between specific microorganisms present in a wound swab.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, microbiological culture results are only available after a few days. Two earlier studies [15,16] have explored the potential of electronic noses to fulfil the need for accurate and fast detection of wound infection in clinical practice. They demonstrated that electronic noses are able to discriminate between specific microorganisms present in a wound swab.…”
Section: Introductionmentioning
confidence: 99%